An Analysis of Core Components of A Teaching Module Based on The Ministry of Education Guidelines And Their Alignment with Learning Objectives: A Descriptive Quantitative Study - Putri Muri Widhi Astika (Faculty of Education, 2025)
This thesis investigates the structure and internal coherence of a Grade X English teaching module, focusing on the extent to which its components—learning objectives, activities, assessments, and media are complete and aligned according to standards outlined in the Merdeka Curriculum. Using a quantitative descriptive approach and a document analysis design, the study evaluates the module through checklists and assessment rubrics to determine both completeness and component alignment. The analysis reveals that all mandatory components (learning objectives, activities, assessments, and learning media) are present and well-developed. The learning objectives are clearly stated, measurable, and reflect cognitive processes across Bloom’s revised taxonomy. Learning activities are organized systematically over two meetings using the Problem Based Learning (PBL) model, integrating engaging and student-centered strategies such as video analysis, group discussions, and storytelling. The assessment component includes both formative and summative measures with clear rubrics for skills, knowledge, and attitudes, ensuring alignment with instructional goals. Learning media include a variety of tools (e.g., YouTube videos, PowerPoint, Google Forms, mobile phones) that support differentiated and technology-integrated instruction. The results show a full alignment between objectives, activities, and assessments, with each component scoring the maximum score of 3, resulting in a total of 9classified as “Excellent.” This confirms the module’s high quality and classroom readiness.
reeapload 2026 Rudi H